Remembering a problematic past: TV mystics, perestroika and the 1990s in post-Soviet media and memory. (June 2017) - Huxtable, Simon
This article examines memories of the TV psychic Anatoly Kashpirovsky, whose TV 'séances' were broadcast on Soviet state television in the late-1980s. Based on the results of interviews from Russians and Ukrainians conducted in 2013–2014, a television serial based on the rise of TV mystics in the late-1980s and a web forum devoted to discussion of the serial, this article uses memories of Kashpirovsky in both vernacular and public contexts as a means of understanding the place of perestroika and the 1990s in the post-Soviet historical consciousness. In particular, the article focuses on the continued contestation over the meaning of perestroika and the 1990s in Russian and Ukrainian collective memory and the different interpretative strategies used to explain the past. The article seeks to examine the different forms of memory work taking place in different memory spaces, from the popular, vernacular memories voiced in interviews, to public memories expressed within popular culture.